AI and Robotics in Futuristic Hospitals - Balasubramanian, M. (British Journal of Healthcare and Medical Research, 2023)
Messy galleries oil painted walls stained bathrooms inefficient staff dim light and noise... This is how we identify a typical Indian hospital. Hospital chains are indeed making their presence felt but for an average Indian branded healthcare is still a luxury. The scenario has to change. The 21st century marks the incoming of technology where everything is changing. Hospitals are no exception. However, the problem is with the strategic perspective.